Metabolomic Profiling, In Vitro Antimalarial Investigation and In Silico Modeling of the Marine Actinobacterium Strain Rhodococcus sp. UR111 Associated with the Soft Coral Nephthea sp. - Noha M. Gamaleldin; Hebatallah S. Bahr; Yaser A. Mostafa; Bryant F. McAllister; Amr El Zawily; Che J. Ngwa; Gabriele Pradel; Hossam M. Hassan; Usama Ramadan Abdelmohsen; Dalal Hussien M. Alkhalifah; Wael N. Hozzein (Antibiotics, 2022)
Malaria is a persistent illness with a great public health concern. To combat this fatal disease, developing effective antimalarial medications has become a necessity. In the present study, we described the actinomycetes associated with the Red Sea soft coral Nephthea sp. and isolated a strain that was sub-cultured in three different media (M1, ISP2, and OLIGO). Actinomycete isolate’s phylogenetic analysis of the 16S rRNA gene revealed that it belongs to the genus Rhodococcus. In vitro screening of the antimalarial activity for three extracts against Plasmodium falciparum was carried out. Non-targeted metabolomics for the chemical characterization of the isolated actinomycete species UA111 derived extracts were employed using high-resolution liquid chromatography–mass spectrometry (LC-HR-MS) for dereplication purposes. Additionally, statistical analysis of the vast LC-MS data was performed using MetaboAnalyst 5.0. Finally, an in silico analysis was conducted to investigate the potential chemical compounds that could be the source of the antimalarial potential. The results revealed that ISP2 media extract is the most effective against Plasmodium falciparum, according to antimalarial screening (IC50 8.5 µg/mL), in contrast, OLIGO media extract was inactive. LC-HRMS-based metabolomics identified a range of metabolites, mainly alkaloids, from the genus Rhodococcus. On the other hand, multivariate analysis showed chemical diversity between the analyzed samples, with ISP2 extract being optimal. The docking analysis was able to anticipate the various patterns of interaction of the annotated compounds with three malarial protein targets (P. falciparum kinase, P. falciparum cytochrome bc1 complex, and P. falciparum lysyl-tRNA synthetase). Among all of the test compounds, perlolyrine (11) and 3097-B2 (12) displayed the best docking profiles. In conclusion, this work demonstrated the value of the established method for the metabolic profiling of marine actinomycetes using the data from liquid chromatography–mass spectrometry (LC-MS), which helps to streamline the difficult isolation stages required for their chemical characterization. In addition, the antimalarial efficacy of this strain has intriguing implications for future pharmaceutical development.